Edukasi Pengetahuan Dan Pencegahan Anemia Pada Remaja SMP Negri 11 Di II Desa Sukasari Kec. Air Periukan Kab. Seluma - Fillah, Iit Mutia; Oktari, Lidya; Radiansyah, Seftiawan; Wulandari, Wulandari (Jurnal Karya Nyata Pengabdian, 2025)
Adolescent girls are a group that is prone to anemia. Adolescent girls are at higher risk of anemia compared to adolescent boys. According to Riskesdas data in 2018, the prevalence of anemia in Indonesia is 48.9% with the proportion of anemia found in the age group of 15-24 years and 25-34 years. Anemia prevention education for adolescent girls aims to provide understanding and knowledge to adolescents about anemia and the impact that will be experienced in adolescents. The target of this activity is adolescent girls at SMPN 11 Seluma, Education is carried out by direct education face-to-face and discussion in the classroom. The result of this activity is that participants understand more about the importance of preventing anemia in adolescents.